Developing a Process-Based Movement Intervention Program and Evaluating Its Effects on the Fundamental Motor Skills and School Readiness of Pre-School Boys - Moslem Rokhfard; Ilnaz Sajjadian; Amir Ghamerani (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Motor skills are needed for entering elementary school. They can students have better performance in learning. The present study aims to develop a process-based movement intervention program and evaluate it efficacy on the fundamental motor skills and school readiness of pre-school boys.Methods This is a quasi-experimental study with a pre-test/post-test/follow-up design. The study population consists of all preschool boys in Isfahan, Iran in 2019-2020. Of these, 30 children with poor motor skills and primary school readiness were selected using a purposive sampling method and randomly divided into experimental and control group. The experimental group received the process-based movement intervention program at 13 sessions. The instruments were Movement Assessment Battery for Children and the Metropolitan Readiness Test. The collected data were analyzed using repeated measures ANOVA.Results The process-based movement intervention had a significant effect on the fundamental motor skills (F=32.94, η2= 0.59, P=0001) and school readiness (F= 46.45, η2= 0.62, P=0001) of pre-school boys.Conclusion The process-based motor intervention program can improve the fundamental motor skills and primary school readiness of pre-school boys by improving balance, sensory systems, motor coordination, and motor programming.